The Relationship Between Arm Muscle Strength And Back Strike Flexibility To Throwing Ability Into The Student Football Game SMP Negeri 19 Makassar - M.Imran Hasanuddin (Journal Physical Health Recreation (JPHR), 2025)
This research is a descriptive analysis research that aims to find out 1) Is there a relationship between arm muscle strength and the ability to throw inside in the football game of SMP Negeri 19 Makassar students.2) Is there a relationship between the flexibility of the backward stroke and the ability to throw into the football game of SMP Negeri 19 Makassar students. 3) Is there a relationship between arm muscle strength and backward flexion together on the ability to throw in the football game of SMP Negeri 19 Makassar students. The population in this study was all male students in grade VIII of SMP Negeri 19 Makassar as many as 95 students, while the sample used was 45 students with a simple random sampling technique. The data from the study was obtained by providing a test of arm muscle strength (30-second push up), back flexibility test and thtow-in test. The data analysis techniques used are descriptive and inferential analysis and requirements tests with data normality tests. Based on the results of statistical analysis, the results of statistical analysis were obtained, among others: 1) There was a relationship between arm muscle strength and throwing ability in football games of SMP Negeri 19 Makassar students, amounting to 23.7%, (r) = 0.487 (Pvalue = 0.001<α 0.05). 2) There was a relationship between backward flex flexibility and the ability to throw inside in football games. SMP Negeri 19 Makassar students, by 26.8%, (r) = 0.518 (Pvalue = 0.000<α 0.05) 3) Is there a relationship between arm muscle strength and backward flex together on throwing ability in the football game of SMP Negeri 19 Makassar students, amounting to 35.3, with a value of (r) = 0.594 (Pvalue = 0.000<α 0.05).